168k views
0 votes
Let h(x) = x + 6 and g(x) = x^2 - 4x + 2
Find h(x) · g(x)

User Yugesh
by
5.5k points

2 Answers

7 votes

Answer:

x³ + 2x² - 22x +12

Explanation:

( x + 6 ) ( x² - 4x + 2 ) = x³ - 4x² + 2x + 6x² - 24x + 12

= x³ + 2x² - 22x +12

User Meatballs
by
4.8k points
6 votes

Answer: x³+2x²-22x+12

Explanation:

the product of functions: (hg)(x)

Use FOIL to solve this (First Outer Inner Later)

(x+6)(x²-4x+2)

=x³-4x²+2x+6x²-24x+12

=x³-4x²+6x²+2x-24x+12

=x³+2x²-22x+12

User Rafaelzlisboa
by
4.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.